Prevention of Peritoneal Metastases from Colon Cancer in High-Risk Patients: Preliminary Results of Surgery plus Prophylactic HIPEC. (8th May 2012) - Sammartino, Paolo; Sibio, Simone; Biacchi, Daniele; Cardi, Maurizio; Accarpio, Fabio; Mingazzini, Pietro; Rosati, Maria Sofia; Cornali, Tommaso; Di Giorgio, Angelo
Abstract : The study compared the outcome in patients with advanced colonic cancer at high risk of peritoneal metastases (mucinous or signet-ring cell) without peritoneal or systemic spread, treated with standard colectomy or a more aggressive combined surgical approach. The study included patients with colonic cancer with clinical T3/T4, any N, M0, and mucinous or signet ring cell histology. The 25 patients in the experimental group underwent hemicolectomy, omentectomy, bilateral adnexectomy, hepatic round ligament resection, and appendectomy, followed by HIPEC. The control group comprised 50 patients treated with standard surgical resection during the same period in the same hospital by different surgical teams. Outcome data, morbidity, peritoneal recurrence rate, and overall, and disease-free survival, were compared. Peritoneal recurrence developed in 4% of patients in the experimental group and 22% of controls without increasing morbidity (P < 0.05 ). Actuarial overall survival curves disclosed no significant differences, whereas actuarial disease-free survival curves showed a significant difference between groups (36.8 versus 21.9 months, P < 0.01 ). A more aggressive preventive surgical approach combined with HIPEC reduces the incidence of peritoneal recurrence in patients with advanced mucinous colonic cancer and also significantly increases disease-free survival compared with a homogeneous control group treated with a standard surgical approach without increasing morbidity.